THE ROLE OF THE POLICE INTELLIGENCE AND SECURITY FIELD IN THE PERFORMANCE OF PAPUA REGIONAL POLICE MEMBERS (POLDA) - Semy B.A Latunussa (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
The purpose of this study is to determine the role of the Police Intelligence and Security sector in the performance of Papua Regional Police (Polda) members, as well as the factors that influence that role. This study employs both normative and empirical jurisprudential research methods. Normative juridical research is conducted using library or secondary material, particularly statute provisions that are aligned with the title and issue description. The study's findings indicate that the National Police's Intelligence and Security sector has not been effective in increasing performance. The results of the research show that the role of the Intelligence and Security sector of the National Police has not been able to play an effective role in improving the performance of members of the Papua Regional Police (Polda), because as the eyes and ears of the leadership, they have not been able to optimally detect early threats and dangers to the security of the headquarters and the safety of the community. This has an impact on the performance of members who Then, the problems that restrict the function of the intelligence sector in boosting the performance of Papua Regional Police (Polda) members include the absence of inter-sector cooperation, where intelligence personnel occasionally operate. Then, the reasons that restrict the function of the intelligence sector in boosting the performance of Papua Regional Police (Polda) members include the absence of inter-sector cooperation, where intelligence members often operate alone to secure targets without telling officers in uniform to secure them. Inappropriate personnel placement factors, namely the placement of intelligence personnel based only on posture and body shape, without regard to adequate intelligence knowledge; and the factor of personnel's relationship with the community, namely a way of interacting with the community, so that they do not control information about their identity to the community.